2008
DOI: 10.1111/j.1745-7254.2008.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra-herb pharmacokinetics interaction between quercetin and isorhamentin

Abstract: Aim: Quercetin and isorhamnetin are common constituents of some herb extracts, such as extracts of gingko leaves and total flavones of Hippophae rhamnoides L. The intra-herb pharmacokinetics interactions between isorhamnetin and quercetin were investigated in the present study. Methods: Human MDR1 cDNA transfected MDCKII cells were used to validate whether isorhamnein interacted with P-gp. Caco-2 transport assays and a randomized, 3-way crossover pharmacokinetics study in rats were used to investigate the phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 34 publications
1
20
1
Order By: Relevance
“…However, in our study, although the major form of Cyp3A , i.e. Cyp3A2 , was not significantly changed, Cyp3A1 and Cyp3A9 were significantly increased in the DMIS rats (Figure ). This was consistent with previous results.…”
Section: Discussioncontrasting
confidence: 63%
“…However, in our study, although the major form of Cyp3A , i.e. Cyp3A2 , was not significantly changed, Cyp3A1 and Cyp3A9 were significantly increased in the DMIS rats (Figure ). This was consistent with previous results.…”
Section: Discussioncontrasting
confidence: 63%
“…1) which was a characteristic of carrier-mediated transport. P-gp was reported to alter the pharmacokinetics of numerous structurally and pharmacologically diverse drugs (Dahan and Amidon 2009;Lan et al 2008). And previous studies had reported that P-gp may be involved in the efflux of lignans compounds (Wang 2009;Hye et al 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Quercetin is mainly carried by albumin (48) and hence, the albumin concentration is a key determinant for the availability of quercetin. Also, quercetin can interact with other bioactive molecules to change its own affinity to albumin (49)(50)(51). Together with the fact that hyperglycemia proportionally declines the affinity of quercetin to albumin (52), which means there remains more quercetin to excrete in severe hyperglycemia than the mild one, it can be assumed that abovementioned inter-trial differences make it difficult to predict if quercetin will decrease the blood glucose in diabetics.…”
Section: Discussionmentioning
confidence: 99%